Developing and validating SARS‐CoV‐2 assays for nonhuman primate surveillance. Issue 5 (6th July 2022) - Yee, JoAnn; Carpenter, Amanda; Nham, Peter; Halley, Bryson; Van Rompay, Koen K. A.; Roberts, Jeffrey
Abstract: Introduction: In early 2020, the California National Primate Research Center implemented surveillance to address the threat of SARS‐CoV‐2 infection in its nonhuman primate colony. Materials/Methods: To detect antiviral antibodies, multi‐antigen assays were developed and validated on enzyme immunoassay and multiplex microbead immunofluorescent assay (MMIA) platforms. To detect viral RNA, RT‐PCR was also performed. Results/Conclusion: Using a 4plex, antibody was identified in 16/16 experimentally infected animals; and specificity for spike, nucleocapsid, receptor binding domain, and whole virus antigens was 95.2%, 93.8%, 94.3%, and 97.1%, respectively on surveillance samples. Six laboratories compared this MMIA favorably with nine additional laboratory‐developed or commercially available assays. Using a screen and confirm algorithm, 141 of the last 2441 surveillance samples were screen‐reactive requiring confirmatory testing. Although 35 samples were reactive to either nucleocapsid or spike; none were reactive to both. Over 20 000 animals have been tested and no spontaneous infections have so far been confirmed across the NIH sponsored National Primate Research Centers.